Ethno-STEM-Based E-Book on Colligative Properties of Solutions to Improve Students' Chemical Literacy and Sustainability Awareness - Harianto, Bibit; Pursitasari, Indarini Dwi; Heliawati, Leny; Syarpin, Syarpin (Journal of Innovation in Educational and Cultural Research, 2026)
This project aims to develop and test Ethno-STEM-based e-books to enhance students’ chemical literacy and sustainability awareness regarding the colligative properties of solutions. The e-book’s development integrates coordination science with local knowledge, enabling students to understand chemical concepts in a relevant and applicable manner. The research strategy employed is RD using the ADDIE model. The e-book was approved by media and content specialists and tested on students to assess its effectiveness in improving chemical education and sustainability awareness. The level of feasibility based on media expert judgment is 89% in the "Valid" category, and media experts are 95% in the "Valid" category. Also, the CVR value is 0.86 and the CVI is 0.93, both of which are in the valid range. E-Books improve students' chemical literacy and sustainability awareness, with N-Gain indices of 0.745 in the "high" category and 0.541 in the "moderate" category—long-term impacts and applications to other disciplines are to be studied to support ESD programs.